Importance of Micronutrient Levels in Specific Populations - Hoyle, Brian (MD Conference Express, 2015)
Micronutrients including vitamins, trace elements, and other compounds are important for brain development and the proper functioning of organs. Depending on the organ, age, and micronutrient, too little or too much of a micronutrient can be deleterious. The consequences may persist and can hinder physical and mental development.